Experimental Study of Hollow-Core Photonic Crystal Fiber Optical Switching Effect in Liquid Nitrogen Environment - Ningfang Song; Yunhao Zhu; Xiaobin Xu; Shijie Xu; Fuyu Gao (IEEE Photonics Journal, 2020)
In this study, the hollow-core photonic crystal fiber (HC-PCF) optical switching effect in liquid nitrogen (LN2) environment is demonstrated and experimentally investigated. Turning off the light transmission is realized by the liquefaction of air present in the airholes of the HC-PCF when the fiber is immersed in LN2, and turning on the light transmission is realized by the evaporation of air when the fiber is taken out of LN2. The extinction ratio of the optical switching effect is found to be ~50 dB; furthermore, the turn-on and turn-off time of the optical switching effect can reach ~8 s and ~3 s, respectively. Thus, optical switching effect in a HC-PCF in LN2 environment can be easily realized, which is beneficial in building all-fiber in-line low-frequency optical-switching systems that can be potentially applied in areas such as fiber sensors.